The triadic brain and its relationship with curiosity, teamwork, and explanation of phenomena in the development of a scientific attitude - Pérez Carrero, Carolina; Rodríguez Moreno, Sandra Milena; Sánchez Mayorga, Lida Del Pilar (Rastros Rostros, 2015)
Purpose: this article analyzes the relationship between three scientific attitudes (curiosity, teamwork and explanation of phenomena) and the triadic brain proposed by Waldemar de Gregori in Construcción familiar-escolar de los tres cerebros [Family school construction of the three brains].Description: a characterization of scientific attitudes in 30 second graders in the science classroom at the Colegio Cundinamarca iedis proposed and performed to contribute to the implementation of strategies that strengthen the scientific attitude of students and thus contribute to learning Natural Sciences.Point of view: such research, with a qualitative, descriptive and interpretive approach, highlights the importance of renewing traditional methodological strategies since the strengthening of attitudes from the classroom enables the development of scientific thought processes.Conclusions: therefore, spaces for interpretation and transformation of reality from the earliest ages of children will be created
Keywords: scientific attitude; social cybernetics; curiosity; triadic brain evolution; explanation of phenomena; teamwork